MOULDING MIXTURES HARDENING PROCESS BASED ON LIGNIN-BASE SULPHONATE BINDER - V. N. Ektova; T. M. Zajats (Литьë и металлургия)
Hardening of agglutinant sands on lignosulphonate binding agent is the result of two processes: oxidation-reduction in the system lignosulphonate acids — persulfuric natrium in the early stages of hardening and hydration of cement in the latter stages.